The diverse pulsational behaviour of β Cep stars: results from long-term monitoring. Issue Volume 9:Issue S301(2013) (18th February 2014) - Handler, G.
Abstract: We studied seven β Cep stars photometrically over the past ten years. Some showed amplitude variations, some frequency changes, and others exhibited stable pulsations, with no consistent picture yet emerging. Additionally, 12 Lac appears to have a 6.7-yr binary companion.